Virtuous Leadership for Social Sustainability: Integrating Psychological Well-Being and Attitudes Towards People with Disabilities in the Workplace - Rodriguez-Araneda, M; Livacic-Rojas, P (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Social sustainability that starts from the workplace is a relevant factor for the achievement of the Sustainable Development Goals. Based on this need, this study analyzes the role of virtuous leadership as facilitator of health and inclusive work environments that integrate followers’ psychological well-being and their attitudes towards people with disabilities. An exploratory design was used with latent variables to assess the proposed virtue-based ethical leadership adjustment model for social sustainability, which presented efficient absolute, comparative, and parsimonious adjustments for its operationalization. In conclusion, virtuous leadership plays a relevant role in the development of followers’ psychological well-being, and attitudes towards people with disabilities in the workplace, contributing to the social sustainability criteria from the work environment. © 2025 by the authors.